Organic X-Ray Image Sensors Using a Medium Bandgap Polymer Donor with Low Dark Current - Ha, Jong Woon; Eom, Seung Hun; Cha, Bo Kyung; Song, Seyeong; Eun, Hyeong Ju; Kim, Jong H.; Park, Jong Mok; Kim, Bong Soo; Park, Byoungwook; Ko, Seo Jin; Yoon, Sung Cheol; Lee, Changjin; et al. (Energy and Environmental Materials, 2024)
The development of portable X-ray detectors is necessary for diagnosing fractures in unconscious patients in emergency situations. However, this is quite challenging because of the heavy weight of the scintillator and silicon photodetectors. The weight and thickness of X-ray detectors can be reduced by replacing the silicon layer with an organic photodetectors. This study presents a novel bithienopyrroledione-based polymer donor that exhibits excellent photodetection properties even in a thick photoactive layer (~700 nm), owing to the symmetric backbone and highly soluble molecular structure of bithienopyrroledione. The ability of bithienopyrroledione-based polymer donor to strongly suppress the dark current density (Jd ~ 10−10 A cm−2) at a negative bias (−2.0 V) while maintaining high responsivity (R = 0.29 A W−1) even at a thickness of 700 nm results in a maximum shot-noise-limited specific detectivity of Dsh* = 2.18 × 1013 Jones in the organic photodetectors. Printed organic photodetectors are developed by slot-die coating for use in X-ray detectors, which exhibit Dsh* = 2.73 × 1012 Jones with clear rising (0.26 s) and falling (0.29 s) response times upon X-ray irradiation. Detection reliability is also proven by linear response of the X-ray detector, and the X-ray detection limit is 3 mA.
Keywords: Band-gap polymers; Emergency situation; Low dark current; Low detection limit; Organic photodetector; Organics; Printable; Silicon photo-detector; X-ray detector; X-ray image sensors; low dark current; low detection limit; organic photodetector; printable; X-ray